Octupole deformation in radium isotopes with the spdf-IBM-1 - Contreras-Corral Pedro A.; Vallejos Omar; Barea José (EPJ Web of Conferences)
We present a preliminary systematic study of the spectroscopic and collective properties of the 216–226Ra isotopic chain in the context of the spdf Interacting Boson Model (spdf-IBM-1). This model includes the octupole degrees of freedom, allowing us to study positive and negative parity states using the same Hamiltonian for all the phenomena studied. By this study, we aimed to reproduce the experimental data for the level energies and the electromagnetic transition rates of these isotopes, while also using a reduced set of parameters.